(NiCr-Cr3C2) / NiCr composite coating and preparation method thereof
By preparing NiCr-Cr3C2 composite coatings using HVOF technology and subjecting them to high-temperature annealing, the problems of decreased hardness and deteriorated corrosion resistance of the coatings at high temperatures were solved. This process formed nanoscale secondary carbides and polycrystalline ring network structures, thereby improving the overall performance of the coatings.
Patent Information
- Application Number
- CN202511102931.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-07
- Publication Date
- 2025-11-11
AI Technical Summary
Existing NiCr-Cr3C2 coatings suffer from decreased hardness and deteriorated corrosion resistance at high temperatures. Coatings prepared by HVOF technology contain unsaturated phases, metastable phases, and microscopic defects, which affect coating performance.
(NiCr-Cr3C2)/NiCr composite coatings were prepared using HVOF technology and subjected to high-temperature annealing in the range of 600-1000℃. The effects of annealing temperature on the microstructure and properties of the coatings were studied using SEM, EDS, XRD and 3D profilometry.
Under annealing at 700℃, the coating forms nanoscale secondary carbides and a polycrystalline ring network structure, exhibiting the highest microhardness, best toughness, and lowest wear rate, thus achieving excellent comprehensive performance.
Smart Images

Figure CN120924895A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite material preparation technology, and particularly relates to a (NiCr-Cr3C2) / NiCr composite coating and its preparation method. Background Technology
[0002] Key components of high-end equipment such as gas turbines, steam turbines, and aero engines are subjected to complex conditions of high-temperature wear, oxidation, and corrosion for extended periods, severely impacting equipment performance and service life. Currently, this problem is primarily addressed by spraying high-temperature resistant ceramic coatings onto the component surfaces, with WC-Co(Cr) and NiCr-Cr3C2 being two typical coating materials. However, WC-Co(Cr) coatings exhibit a sharp decrease in hardness and deterioration in corrosion resistance above 530℃, while NiCr-Cr3C2 coatings, due to the high-temperature stability of the Cr3C2 phase and the excellent oxidation resistance of the NiCr bonding phase, have been widely used in energy and aerospace fields. The coating is mainly prepared using technologies such as atmospheric plasma spraying, laser cladding, HVOF, and HVAF. Among them, HVOF technology, with its unique kinetic-thermal coupling deposition characteristics (particle velocity > 600 m / s, temperature < 1800℃), can effectively inhibit the decarburization and decomposition of the Cr3C2 phase, producing a high-quality coating with low porosity and high bonding strength, enabling the coating to maintain excellent high-temperature wear resistance and corrosion resistance even at 900℃. However, NiCr-Cr3C2 coatings prepared by HVOF technology usually contain unsaturated phases, metastable phases, microscopic defects, and residual stress. This inhomogeneity of the microstructure significantly affects the coating performance. Summary of the Invention
[0003] To address the aforementioned technical problems, this invention proposes a (NiCr-Cr3C2) / NiCr composite coating and its preparation method. A (NiCr-Cr3C2) / NiCr composite coating with a compositional gradient was prepared using HVOF technology. Then, the coating samples were subjected to high-temperature annealing at five temperatures (600℃, 700℃, 800℃, 900℃, and 1000℃) using a high-temperature embedding method (sealed with Al2O3-SiO2 refractory mortar) for 120 minutes, followed by furnace cooling. By comprehensively utilizing various characterization techniques (SEM, EDS, XRD, and 3D profilometry) and mechanical property analysis (hardness, toughness, and friction and wear properties), the influence of annealing temperature on the evolution of coating phase composition, reconstruction of nanoscale structure, and mechanical properties was systematically studied.
[0004] To achieve the above objectives, the present invention provides the following technical solution:
[0005] A method for preparing a (NiCr-Cr3C2) / NiCr composite coating includes the following steps:
[0006] Using HVOF (High-speed oxygen fuel spraying) technology, NiCr powder and NiCr-Cr3C2 powder are sequentially sprayed onto the surface of the substrate to form a NiCr transition layer and a NiCr-Cr3C2 working layer, respectively; then annealing is performed to obtain the (NiCr-Cr3C2) / NiCr composite coating.
[0007] Optionally, the NiCr powder and NiCr-Cr3C2 powder need to be dried in an oven at 270°C for 6 hours before spraying to fully remove moisture from the powder and ensure the stability of the spraying process and the quality of the coating.
[0008] Optionally, the base material is 20CrMo steel with dimensions of 15×15×12mm.
[0009] Furthermore, the substrate needs to undergo surface pretreatment before spraying:
[0010] First, sandblasting is performed to achieve a surface roughness of Ra 3.8-5.3μm to enhance the adhesion between the coating and the substrate. Then, the substrate is preheated (preheating temperature is 400-600℃) to reduce thermal stress during the spraying process and prevent cracking.
[0011] Optionally, the conditions for spraying NiCr powder are as follows:
[0012] The powder feed rate is 56-60 g / min, the oxygen flow rate is 1890 LPM, the propylene flow rate is 7 LPM, the air flow rate is 21 LPM, the distance between the spray gun and the substrate is 350 mm, and the lateral movement speed of the spray gun is 500 mm / s.
[0013] Furthermore, the thickness of the NiCr transition layer is 50 μm.
[0014] Optionally, the conditions for spraying NiCr-Cr3C2 are as follows:
[0015] The powder feed rate is 56-60 g / min, the oxygen flow rate is 1920 LPM, the propylene flow rate is 7 LPM, the air flow rate is 26 LPM, the injection distance is 300 mm, and the lateral velocity is 500 mm / s.
[0016] Furthermore, the thickness of the NiCr-Cr3C2 working layer is 150 μm.
[0017] Optionally, the annealing process includes the following steps:
[0018] The substrate coated with the NiCr transition layer and NiCr-Cr3C2 working layer was sealed and wrapped with Al2O3-SiO2 refractory mortar (produced by Zhejiang Jiaxing Huafeng Refractory Materials Co., Ltd.) to prevent the coating from oxidizing at high temperature.
[0019] Subsequently, it was placed in an SX2-12-12A box-type resistance furnace and annealed at 600℃-1000℃ for 120 minutes.
[0020] After annealing, turn off the furnace power and allow it to cool to room temperature to avoid thermal stress or cracks caused by rapid cooling.
[0021] Furthermore, the annealing temperature is 700°C.
[0022] A (NiCr-Cr3C2) / NiCr composite coating is prepared by the above preparation method.
[0023] Optionally, the hardness of the (NiCr-Cr3C2) / NiCr composite coating is 1242 HV. 0.2 Its toughness is 7.9 MPa·m 1 / 2 The wear rate is 0.37 × 10⁻⁶. -5 mm 3 / N·m.
[0024] Compared with the prior art, the present invention has the following advantages and technical effects:
[0025] This invention employs HVOF technology to prepare (NiCr-Cr3C2) / NiCr composite coatings, and performs annealing treatment at five selected temperatures within a wide temperature range of 600-1000℃. Finally, the influence mechanism of temperature on the microstructure and properties of the coating is systematically studied by characterization methods such as SEM, EDS, XRD, and 3D profilometry combined with mechanical property testing.
[0026] After the annealing treatment specified in this invention, annealing at 700℃ can form nanoscale secondary carbides and a "polycrystalline ring" network structure, enabling the coating to obtain optimal comprehensive performance, namely the highest coating cross-sectional microhardness (1242 HV). 0.2 ), with optimal toughness (7.9 MPa·m) 1 / 2 ) and minimum wear rate (0.37×10 -5 mm 3 / N·m). Attached Figure Description
[0027] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:
[0028] Figure 1The images show the particle size distribution and phase analysis of NiCr-Cr3C2 and NiCr powders, where (a) is the SEM image of NiCr powder, (b) is the particle size distribution of NiCr powder, (c) is the SEM image of NiCr-Cr3C2, (d) is the particle size distribution of NiCr-Cr3C2 powder, and (e) is the XRD pattern of NiCr-Cr3C2 powder.
[0029] Figure 2 The images show the cross-sectional morphology and phase composition of the sprayed coating; where (a) is a low-magnification SEM image of the cross-section of the sprayed coating, (b) is a high-magnification SEM image of the cross-section of the sprayed coating, (c) is the XRD pattern of the surface of the sprayed coating, and (d) is the EDS line scan image of the sprayed coating.
[0030] Figure 3 XRD patterns of coatings annealed at different temperatures;
[0031] Figure 4 The images show the SEM-EDS analysis of the coatings after annealing at 600℃ and 700℃, where (a) and (b) represent 600℃ and (c)-(g) represent 700℃.
[0032] Figure 5 The images show SEM-EDS analysis of the cross-section of the coating after annealing at 800℃; (a) is a SEM image of the coating cross-section magnified 600 times, (b) is a SEM image of the coating cross-section magnified 7000 times, (c) is a SEM image of the coating cross-section magnified 20000 times, (d) is a SEM image of the interface between the NiCr-Cr3C2 coating and the NiCr coating magnified 5000 times, and (e) is a SEM image of the NiCr coating magnified 15000 times.
[0033] Figure 6 The images show the microstructure and EDS analysis of the coatings after annealing at 900℃ and 1000℃, where (a)-(c) represent 900℃ and (d)-(f) represent 1000℃.
[0034] Figure 7 The images show the morphological features of wear marks on coatings after annealing at different temperatures; where (a) is a 3D morphological image of the wear mark, (b) is a bar chart of the wear volume, and (c) is a curve of the wear mark depth.
[0035] Figure 8 The friction and wear curves (a) and wear rate bar graphs (b) of the coating in the sprayed state and after annealing at different temperatures are shown.
[0036] Figure 9 The hardness (a) and fracture toughness (b) of the coating after annealing at different temperatures are shown.
[0037] Figure 10The images show the tribological morphology of the sprayed coating and the annealed coating at 600℃, where (a)-(c) represent the sprayed coating and (d)-(g) represent the annealed coating at 600℃.
[0038] Figure 11 The images show the tribological morphology of the coatings annealed at 700℃ and 800℃, where (a)-(c) are the coatings annealed at 700℃ and (d)-(g) are the coatings annealed at 800℃.
[0039] Figure 12 The images show the wear track morphology of coatings annealed at 900℃ and 1000℃ after friction and wear tests at room temperature. (a)-(d) are coatings annealed at 900℃, and (e)-(g) are coatings annealed at 1000℃. Detailed Implementation
[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0041] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0042] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0043] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0044] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0045] Unless otherwise specified, "room temperature" in this invention refers to 20-30℃.
[0046] All raw materials used in this invention were purchased from the market. The two HVOF spraying powders used in the following examples, sintered Ni80Cr (hereinafter referred to as "NiCr") and 25NiCr-75Cr3C2 (hereinafter referred to as "NiCr-Cr3C2") powders, were both purchased from Chongyi Zhangyuan Tungsten Industry Co., Ltd.
[0047] Figure 1 The particle size distribution and phase analysis of NiCr-Cr3C2 and NiCr powders are shown in the figures. (a) is the SEM image of NiCr powder, (b) is the particle size distribution of NiCr powder, (c) is the SEM image of NiCr-Cr3C2 powder, (d) is the particle size distribution of NiCr-Cr3C2 powder, and (e) is the XRD pattern of NiCr-Cr3C2 powder. The figures show that the NiCr powder is spherical / elliptical with an average particle size of 37.10 ± 15.19 μm; the NiCr-Cr3C2 powder has a hollow spherical structure (average particle size of 22.19 ± 6.06 μm) and is composed of two phases: NiCr and Cr3C2. Its surface is uneven and contains a certain number of pores. This unique structure significantly improves thermal conductivity, which helps to achieve rapid heating during the spraying process.
[0048] The technical solution of the present invention will be further illustrated by the following embodiments.
[0049] Example 1
[0050] A method for preparing a (NiCr-Cr3C2) / NiCr composite coating includes the following steps:
[0051] (1) Substrate pretreatment: The substrate material used is 20CrMo steel (size is 200×200×12mm). After quenching (quenching temperature is 850℃, quenching time is 60min) and tempering (tempering temperature is 520℃, tempering time is 120min) heat treatment, the substrate surface is polished and cleaned with acetone to thoroughly remove surface contaminants.
[0052] (2) Coating prepared using the JP8000 high-velocity flame spraying system (HVOF technology):
[0053] Before spraying, NiCr and NiCr-Cr3C2 powders were dried at 270℃ for 6 hours, and the substrate was sandblasted (Ra3.8-5.3μm) and preheated (preheating temperature is 400-600℃).
[0054] During spraying, a 50μm thick NiCr conversion layer is first deposited, followed by a 150μm thick NiCr-Cr3C2 working layer; at the same time, compressed air is used for cooling to control deformation.
[0055] After the coating process was completed, 50 samples measuring 15×15×12mm were prepared using a wire cutting device for subsequent research. The specific coating process parameters are shown in Table 1.
[0056] Table 1
[0057]
[0058] (3) Annealing
[0059] Annealing was performed in a box-type resistance furnace of type SX2-12-12A: 50 HVOF coating samples (15×15×12mm in size) were divided into 5 groups (10 samples in each group), sealed with Al2O3-SiO2 refractory mortar (produced by Zhejiang Jiaxing Huafeng Refractory Materials Co., Ltd.), and the samples were annealed at 600℃, 700℃, 800℃, 900℃ and 1000℃ for 120 minutes respectively, and then cooled in the furnace.
[0060] Effect verification
[0061] I. Friction and Wear Test
[0062] Ball-disc wear tests were performed on the sprayed coating (the coating obtained after spraying in step (2)) and the annealed coating sample (the coating sample obtained after annealing in step (3)) using an MPT-3G friction and wear tester (according to ASTM G-99 standard).
[0063] The experimental conditions were as follows: At room temperature, 6mm diameter alumina spheres were used as a control, and a load of 15N was applied. The wear diameter was 4mm, the rotation speed was 200 rpm, and the test duration was 120 minutes. After the test, the wear volume and wear trajectory morphology were measured using a 3D profilometer, and the wear rate was calculated using the following formula:
[0064]
[0065] In the formula, W represents the wear rate (mm). 3 / Nm), Vc represents the wear volume (mm). 3 L represents the applied force (N), and S represents the sliding displacement (m).
[0066] II. Characterization
[0067] Multiple testing methods were used to analyze the material properties:
[0068] SEM-EDS analysis was performed using a JSM-7610FPlus scanning electron microscope.
[0069] The hardness of the coating cross section was tested using an HXD-1000 microhardness tester (200 g / 15 sec, average of 10 measurements).
[0070] Fracture toughness was assessed using a CSI-TE048 hardness tester (100 kg / 10 sec) (calculated according to the formulas of Evans and Wilshaw).
[0071] Porosity and particle size distribution were analyzed using ImageJ software, and phase analysis was performed using D8 Advance XRD (copper Kα, λ=1.54056Å, 20°–100°, 0.02° / step, 2° / min, 40kV / 40mA). Wear morphology and volume were characterized using a Leica DCM8 white light interferometric microscope (3D height gauge).
[0072] Figure 2 The cross-sectional morphology and phase composition of the sprayed coating are shown (green arrows indicate molten Cr3C2; yellow arrows indicate unmelted Cr3C2); where (a) is a low-magnification SEM image of the cross-section of the sprayed coating, (b) is a high-magnification SEM image of the cross-section of the sprayed coating, (c) is the XRD pattern of the surface of the sprayed coating, and (d) is the EDS line scan of the sprayed coating. The coating adopts a double-layer structure design: the outer layer is a 150 μm thick NiCr-Cr3C2 coating (porosity of approximately 2%), and the inner layer is a 50 μm thick NiCr coating. Figure 2 Phase analysis in (c) shows that the NiCr-Cr3C2 coating consists of a NiCr binder phase, a Cr3C2 phase, and a small amount of Cr7C3 phase, with some of the Cr3C2 phase fused into the NiCr phase. Figure 2 (b) The NiCr coating exhibits a dense and uniform microstructure (grain size 1-4 μm), with almost no pores or impurities. Figure 2 (b)). EDS line scan results ( Figure 2 As shown in (d), the chromium and nickel content at the interface transitions smoothly, confirming a good metallurgical bond between the coatings.
[0073] Figure 3 XRD patterns of coatings annealed at different temperatures; by analyzing... Figure 3 Phase analysis of the coating after annealing at 600-1000℃ revealed that the coating was consistently composed mainly of Cr3C2 and NiCr phases, with (Cr,Ni)7C3 and Cr also detected. 23The presence of two secondary carbides, C6 and C7, was observed. The results indicate that the original Cr3C2 phase did not undergo significant decarburization during annealing. Instead, the molten or semi-molten Cr3C2 phase during spraying underwent a solid-state phase transformation to form (Cr,Ni)7C3 secondary carbides. Furthermore, the NiCr binder phase contains a certain amount of C atoms, which readily precipitate (Cr,Ni)7C3 particles during annealing. As the annealing temperature increased from 600℃ to 1000℃, the amount of (Cr,Ni)7C3 phase formed showed a continuously increasing trend, and some of the (Cr,Ni)7C3 phase further transformed into (Cr,Ni). 23 The C6 phase exhibits a clear temperature dependence in its phase transition behavior.
[0074] Figure 4 The cross-sectional microstructure and EDS analysis results of the coatings after annealing at 600℃ and 700℃ are shown in Table 2 (yellow arrows indicate ceramic phase; green arrows indicate secondary carbides; blue arrows indicate network structure; EDS analysis results are shown in Table 2), where (a) and (b) are at 600℃, and (c)-(g) are at 700℃. Under the annealing condition of 600℃, the porosity of the NiCr-Cr3C2 coating decreased from 2% in the deposited state to 1.5%. Figure 2 (a) and Figure 4 In the middle (a) phase, fine secondary carbides precipitated in the NiCr phase. EDS analysis ( Figure 4 Tables (b) and (2) show that the Cr / C atomic ratio of the bulk ceramic phase is approximately 1.8, falling between the atomic ratios of Cr3C2 (1.5) and Cr7C3 (2.33), but closer to Cr3C2 (1.5). This suggests that the Cr3C2 in the coating has not undergone significant decarburization. Notably, a 5-10 μm carbon-rich phase (with a carbon content as high as 85.3 at%) appears in the coating. Its formation mechanism can be attributed to the diffusion and aggregation effect of carbon atoms catalyzed by Ni, ultimately forming a graphite phase. Studies indicate that this graphite phase generally coexists with Cr3C2 and Ni, negatively impacting the coating's performance.
[0075] When the annealing temperature is increased to 700℃, the densification of the coating is further improved, and the porosity decreases to 0.5%. Figure 4 (c)). Microstructural analysis shows that a unique submicron-scale network structure is formed in the NiCr phase. Figure 4 In section (f), this structure originates from the recrystallization of high-density dislocations generated during HVOF preparation at the recrystallization temperature (700℃), ultimately forming a continuous "polycrystalline ring" network structure. Furthermore, finely dispersed nanoscale particles were also observed in the NiCr-Cr3C2 coating. Figure 4The medium (g) phase was identified by EDS analysis as a newly formed (Cr,Ni)7C3 phase. Furthermore, the Cr / C atomic ratio of the bulk ceramic phase increased to 1.9, indicating that high temperature promoted the transformation of Cr3C2 to Cr7C3. In contrast, the NiCr coating remained stable at both annealing temperatures of 600℃ and 700℃, showing no significant changes in microstructure.
[0076] Figure 5 SEM-EDS analysis of the cross-section of the coating after annealing at 800℃ is shown in Table 2. The NiCr-Cr3C2 coating maintains a density comparable to the sample annealed at 700℃, with a porosity of approximately 0.6%. Figure 5 In the middle (a)), a large amount of secondary carbides precipitated in the NiCr binder phase ( Figure 5 (b)). EDS analysis ( Figure 5 Tables (b) and (2) show that the Cr / C atomic ratio in the ceramic phase is 1.86, indicating that a small portion of Cr3C2 underwent a decarburization reaction to form Cr7C3. Spherical, cracked, shell-like structures of 150-500 nm also appeared in the coating. Figure 5 In the middle (c), the carbon content reaches 52.6 at%, which may be because the free carbon after the decomposition of Cr3C2 (Cr3C2→Cr7C3+C) forms a graphite layer driven by surface energy, and cracks occur due to the difference in thermal expansion during cooling. In addition, the NiCr interlayer forms a 50-200 nm Cr-enriched spherical structure after annealing at 800℃. Figure 5 (d) and (e)). This phenomenon originates from the amplitude-modulated decomposition that occurs after the NiCr alloy enters the metastable region: Cr atoms diffuse and aggregate towards grain boundaries / dislocations, while the rapid diffusion of Ni generates vacancies, which together promote the nanoscale aggregation of Cr.
[0077] Figure 6 Microscopic morphology and EDS analysis of the coatings after annealing at 900℃ and 1000℃ are shown, where (a)-(c) represent 900℃ and (d)-(f) represent 1000℃. After annealing at 900℃, the NiCr-Cr3C2 coating maintained a high density (porosity 0.75%), and the secondary carbides in its NiCr binder phase showed significant aggregation and growth. Figure 6 (b)). The Cr / C atomic ratio of the bulk ceramic phase remained between 1.8 and 1.9 (Table 2), which to some extent confirms that Cr3C2 is relatively stable and has not shown significant decarburization reaction, consistent with the XRD results. Meanwhile, the number of Cr nanoclusters generated by amplitude modulation decomposition in the NiCr interlayer increased significantly compared to 800℃. Figure 6(c) When the annealing temperature rises to 1000℃, the coating density increases significantly (porosity decreases to 0.3%), and the microstructure undergoes significant changes: compared to 900℃, the particulate secondary carbides precipitated at high temperatures in the NiCr-Cr3C2 coating aggregate and fuse into continuously distributed bulk carbides ( Figure 6 In the middle (e), these carbides are tightly connected and significantly compress the NiCr binder phase space. EDS analysis shows that the Cr / C atomic ratio of the bulk ceramic phase in the coating decreases to 2.0, which may be due to the sufficient diffusion of Ni atoms at high temperature, effectively promoting the formation of the (Cr,Ni)7C3 phase. Notably, the number and size of Cr nanoclusters in the NiCr interlayer not only increased after treatment at 1000℃, but also increased significantly. These structural evolutions reveal the phase transformation behavior and element diffusion characteristics of the coating material during high-temperature annealing.
[0078] Table 2. EDS (Energy Dispersive Spectroscopy) Analysis Results (Atomic Percentage)
[0079]
[0080]
[0081] Note: Regions 1-4 are... Figure 4 The proportions of different elements measured at different locations in (b) are similar to those in other cases.
[0082] Figure 7 Morphological characteristics of wear marks on coatings after annealing at different temperatures (Figures) Figure 7 In (b), 0℃ on the x-axis represents the unannealed sample; where (a) is the 3D morphology of the wear track, (b) is the wear volume histogram, and (c) is the wear track depth curve. As can be seen from the figures, the 700℃ annealed coating has the shallowest wear track (approximately 2.2 μm deep), exhibiting the best wear resistance; the 900℃ annealed coating is second (2.6 μm), with slightly lower wear resistance than the 700℃ sample. The sprayed (3.2 μm) and 1000℃ annealed (4.5 μm) coatings show significantly increased wear track depths, further reducing wear resistance. The 600℃ and 800℃ annealed coatings exhibit the most severe wear (wear depths of 10.2 μm and 8.8 μm, respectively). Notably, the 600℃ annealed coating has a wear track depth exceeding 10 μm, exhibiting the worst wear resistance. These wear track depth data are in perfect agreement with the tribological test results of each coating, further confirming the significant effect of 700℃ heat treatment on improving the wear resistance of the coating.
[0083] Figure 8The figures show the friction and wear curves (a) and wear rate bar graphs (b) of the coating in the sprayed state and after annealing at different temperatures. In (b), 0℃ on the x-axis represents the unannealed sample. The figures show that the coating annealed at 700℃ exhibits the best wear resistance, with the lowest average coefficient of friction (0.13) and the smallest wear rate (0.37 × 10⁻⁶). -5 mm 3 / N·m). The 900℃ annealed coating is the second best (friction coefficient 0.21, wear rate 0.51×10). -5 mm 3 / N·m), its performance is similar to that of the sprayed state (0.22, 0.59×10 -5 mm 3 / N·m) and 1000℃ annealed coating (0.24, 0.57×10 -5 mm 3 The ratio ( / N·m) is comparable. In contrast, at 800℃ (0.29, 1.21×10) -5 mm 3 / N·m) and 600℃ annealed coating (0.34, 1.82×10 -5 mm 3 The wear resistance of the coating (N·m) decreased significantly. The results showed that annealing at 700℃ significantly improved the wear resistance of the coating, while the coatings annealed at 600℃ and 800℃ had the worst wear resistance. The wear resistance of the coatings annealed at 900℃ and 1000℃ was similar to that of the sprayed coating, which was at a medium level.
[0084] Figure 9 The figures show the hardness (a) and fracture toughness (b) of the coatings after annealing at different temperatures. As can be seen from the figures, the NiCr-Cr3C2 coating annealed at 700℃ exhibits the highest hardness, which stems from three synergistic strengthening mechanisms: densification effect resulting from reduced porosity to 0.5%, precipitation strengthening of nanoscale secondary carbides in the NiCr phase, and strengthening through recrystallization forming submicron-level "polycrystalline ring" structures. The coating annealed at 600℃ has the second highest hardness due to incomplete densification and limited secondary precipitation. Notably, when the temperature rises to 900-1000℃, the microhardness significantly decreases due to partial decarburization of Cr3C2 into the (Cr,Ni)7C3 phase and coarsening of secondary carbides. For the NiCr intermediate layer, its hardness shows a monotonically decreasing trend with increasing temperature, especially exhibiting a sharp softening above 800℃. This is directly related to the precipitation of Cr atoms from the NiCr solid solution during amplitude modulation decomposition (forming 50-200nm Cr aggregates), which significantly weakens the solid solution strengthening effect.
[0085] Fracture toughness is an important mechanical property indicator used to measure the crack propagation resistance of composite coatings. Among these, the Vickers indentation method is widely considered one of the most accurate experimental methods for evaluating the fracture toughness of ceramic substrate coatings. The calculation formula used in this invention is as follows:
[0086]
[0087] In the formula K IC Fracture toughness (MPa·m) 1 / 2 P is the applied load (Newtons), a is half the diagonal length of the indentation (μm), and c represents the distance from the center of the indentation to the crack tip (μm). The results calculated according to the above formula are as follows: Figure 9 As shown in Figure (b), the coating annealed at 700℃ exhibits the best overall performance, with the highest fracture toughness (K). IC =7.9 MPa·m 1 / 2 HV 100 Hardness reaches 510, HV 30 The hardness value reaches 591, attributed to its ideal microstructure features: moderate secondary carbide precipitation, a uniform NiCr recrystallization network, and optimized density. Properties significantly decrease after annealing at 800℃ (K). IC =5.0, HV 100 =366, HV 30 =455), mainly due to the formation of submicron-sized spherical cracked shell structures that disrupt the continuity of the ceramic phase. Although the performance of the coatings annealed at 900℃ and 1000℃ is reduced due to secondary carbide coarsening and Cr3C2 decarburization transformation, it still maintains a high level (K). IC The values are 7.0 and 5.8 respectively, HV 100 The values were 488 and 491 respectively, which is attributed to improved coating density and compositional homogenization. Spray-coated coatings, due to the presence of numerous pores, dislocations, and residual stresses, exhibit poor fracture toughness (K0). IC =5.4) and the lowest maximum load hardness (HV) 100 =367), these defects promote the initiation and rapid propagation of microcracks. Test results show that annealing at 700℃ effectively improves the coating's resistance to crack propagation while maintaining its high hardness, achieving an optimal balance between strength and toughness. These findings provide important evidence for understanding the structure-property relationship between heat treatment temperature, microstructure, and mechanical properties.
[0088] Figure 10The figures show the tribological morphology of the sprayed coating and the 600℃ annealed coating (blue arrows represent carbon-rich phases; EDS analysis results are shown in Table 3), where (a)-(c) represent the sprayed coating and (d)-(g) represent the 600℃ annealed coating. As can be seen from the figures, the sprayed coating exhibits typical adhesive-slip wear characteristics, with a shallow wear track width of approximately 580 μm. Figure 10 In the middle (a), a periodic wavy structure is formed on the surface, and material accumulation and micro-cutting marks are visible at the troughs. Figure 10 (b)). This morphology originates from an intermittent adhesion-tear wear mechanism, while the interfacial thermal stress mismatch caused by frictional heat triggers network cracks and surface oxidation. Figure 10 (b) and Figure 10 (c)). In contrast, although the wear mark width was similar (570 μm) for the 600℃ annealed coating, the wear depth increased significantly and flaking occurred. Figure 10 (middle (d)). High-magnification observation revealed a carbon-rich phase in the exfoliated area similar to that in the cross-section. Figure 10 (e) and Figure 4 (b) The morphology and composition characteristics (Table 3) confirm that it is a graphite phase, which significantly weakens the coating adhesion and promotes the initiation of annular cracks. Figure 10 In the middle (f), the flaking eventually leads to the peeling of the plaques. It is noteworthy that, apart from the peeled areas, the wear in the remaining areas is relatively uniform, indicating that the flaking of the plaques induced by the graphite phase is the main reason for the deterioration of the wear resistance of the coating annealed at 600℃. This finding reveals the key mechanism by which the graphite phase formed during the heat treatment process affects the tribological properties of the coating.
[0089] Figure 11 The figures show the tribological morphology of the coatings annealed at 700℃ and 800℃, where (a)-(c) represent the coatings annealed at 700℃, and (d)-(g) represent the coatings annealed at 800℃. As can be seen from the figures, the 700℃ annealed coating exhibits excellent wear resistance, with a wear track width of approximately 560 μm (slightly smaller than the sprayed and 600℃ annealed samples), and the shallowest wear depth (compared to...). Figure 8 The conclusions are consistent. Microscopic observation shows that the surface of the wear marks is smooth, with only slight plastic deformation and surface oxidation. Figure 11 In (b) and (c), the ceramic phase and binder phase interfaces are firmly bonded with no detachment. In contrast, although the wear track width of the 800℃ annealed coating further decreased to 530 μm, the wear depth increased significantly, and a large amount of brittle spalling and fish-scale-like lamellar peeling occurred. Figure 11 In the middle (e)-(g)), these flaked debris act as abrasive particles, exacerbating secondary wear. It is noteworthy that while the 800℃ annealed coating exhibits a reduction in wear track width (approximately 530 μm), its wear depth significantly increases. Figure 8(As shown). This seemingly contradictory phenomenon stems from its unique wear mechanism: during wear, brittle spalling fragments easily aggregate at the bottom of the wear track, forming third-body abrasive grains. This three-body wear mechanism leads to a significant increase in wear track depth. Simultaneously, the presence of spalling fragments reduces frictional contact at the wear track edges, resulting in a relative decrease in wear track width. This phenomenon reveals a complex nonlinear relationship between the coating's wear resistance and its microstructure, indicating that wear resistance cannot be accurately assessed solely based on wear track width; a comprehensive analysis combining wear depth and microstructure is necessary. Essentially, this unique wear behavior originates from the submicron-scale spherical cracked shell structure formed by annealing at 800℃. This structural feature not only disrupts the continuity of the ceramic phase, becoming the primary nucleation site for microcracks, but also significantly reduces the coating's fracture toughness and cohesive strength, while altering its tribological characteristics.
[0090] Figure 12 The figures show the wear track morphology of coatings annealed at 900℃ and 1000℃ after friction and wear tests at room temperature. (a)-(d) represent coatings annealed at 900℃, and (e)-(g) represent coatings annealed at 1000℃. As can be seen from the figures, the wear track width of the coating annealed at 900℃ is significantly reduced to 390μm, and its wear morphology exhibits three typical characteristics: a uniform wear zone dominated by plastic deformation (…). Figure 12 (c) and oxide zones with network cracks Figure 12 (d) and the spalling area concentrated in the center of the wear marks ( Figure 12 (b)). This morphological feature originates from the large contact stress in the central region of the wear track, leading to more severe wear, plastic deformation, and coating peeling, while the excellent combination of hardness and toughness ( Figure 9 This allows the edge region to effectively resist fatigue damage caused by shear and tensile stress. Notably, the micron-sized pits appearing in the spalled area indicate that the material retains a certain degree of plastic deformation capacity during failure. In contrast, the wear mark width of the coating annealed at 1000℃ significantly increased to 590 μm. Figure 12 In the middle (e), its wear mechanism undergoes a significant change: the mechanical properties decrease due to the aggregation and growth of carbides. Figure 9 This makes the inner side of the wear track more prone to fatigue spalling under complex stress conditions, forming an edge spalling zone characterized by quasi-cleavage structure. Figure 12 In the middle (f)); while the area near the outer edge is dominated by compressive stress and plastic deformation, exhibiting a uniform wear morphology with slight oxidation. Figure 12 (g) This comparison reveals the inherent law that heat treatment temperature affects the wear mechanism of coatings by regulating their microstructure.
[0091] Table 3. EDS energy dispersive spectroscopy analysis results (atomic percentage)
[0092] EDSarea Ni Cr C O 1( Figure 10 (c) 8.5 26.8 24.0 40.7 2( Figure 10 (e) 12.2 34.2 50.1 3.5 3( Figure 10 (e) 6.1 21.5 68.3 4.1 4( Figure 10 (g) 14.0 39.9 44.5 1.6 5( Figure 11 (c) 9.3 28.9 47.0 14.8 6( Figure 11 (g) 9.3 27.8 43.8 19.1 7( Figure 12 (c) 8.8 30.2 45.0 16.0 8( Figure 12 (g) 8.9 31.2 49.9 10.0
[0093] In summary, this invention successfully prepared a NiCr-Cr3C2 composite coating using high-velocity flame spraying (HVOF) technology, and annealed it at five temperature gradients (600℃, 700℃, 800℃, 900℃, and 1000℃) within the range of 600-1000℃. The aim is to reveal the influence of different annealing temperatures on the evolution of the coating phase composition, the reconstruction of the nanoscale structure, and the mechanical properties, providing an important theoretical basis for optimizing coating performance.
[0094] As the annealing temperature increases, the trend of Cr3C2 in the coating decarburizing and transforming into the (Cr,Ni)7C3 phase becomes more and more obvious. At the same time, the amount of (Cr,Ni)7C3 secondary carbides precipitated in the NiCr binder phase not only increases significantly, but their size also shows a continuous increase.
[0095] The coating annealed at 700℃ exhibits the best overall performance, with the highest cross-sectional microhardness and the best fracture toughness (7.9 MPa·m). 1 / 2 It also possesses the best wear resistance. Although the hardness of the coating is reduced slightly after annealing at 900℃, it maintains good toughness (7.0 MPa·m). 1 / 2 The coatings annealed at 1000℃ and those applied by spraying exhibited good wear resistance. The wear resistance of both the annealed and sprayed coatings was at a moderate level. In contrast, the coating annealed at 600℃ showed the worst toughness and wear resistance, while the coating annealed at 800℃ showed slightly better toughness and wear resistance than the 600℃ sample but was still significantly worse than samples treated at other temperatures.
[0096] Annealing at 700℃ promotes the formation of a large number of nanoscale secondary carbides within the coating, while the NiCr binder phase recrystallizes to form a continuous "polycrystalline ring" network structure. This optimized microstructure significantly improves the overall performance of the coating. In contrast, annealing at 600℃ leads to the formation of micron-sized graphite phases, causing severe lamellar spalling during wear; while annealing at 800℃ produces a large number of ellipsoidal cracked shell structures, resulting in significant brittle spalling behavior and a sharp decline in wear resistance.
[0097] As the annealing temperature increases, significant amplitude-modulated decomposition occurs in the NiCr interlayer, leading to the precipitation of Cr atoms from the solid solution and the formation of nanoscale Cr agglomerates. Particularly under high-temperature annealing conditions above 800℃, the size of these Cr agglomerates increases significantly, severely weakening the solid solution strengthening effect of the NiCr alloy. This directly results in a significant monotonic decrease in the hardness of the NiCr interlayer with increasing annealing temperature.
[0098] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a (NiCr-Cr3C2) / NiCr composite coating, characterized in that, Includes the following steps: High-speed oxygen fuel spraying technology is used to sequentially spray NiCr powder and NiCr-Cr3C2 powder onto the surface of a substrate to form a NiCr transition layer and a NiCr-Cr3C2 working layer, respectively; then annealing is performed to obtain the (NiCr-Cr3C2) / NiCr composite coating.
2. The method for preparing a (NiCr-Cr3C2) / NiCr composite coating according to claim 1, characterized in that, The NiCr powder and NiCr-Cr3C2 powder need to be dried in an oven at 270°C for 6 hours before spraying.
3. The method for preparing a (NiCr-Cr3C2) / NiCr composite coating according to claim 1, characterized in that, The base material is 20CrMo steel.
4. The method for preparing a (NiCr-Cr3C2) / NiCr composite coating according to claim 1, characterized in that, The conditions for spraying NiCr powder are as follows: The powder feed rate is 56-60 g / min, the oxygen flow rate is 1890 LPM, the propylene flow rate is 7 LPM, the air flow rate is 21 LPM, the distance between the spray gun and the substrate is 350 mm, and the lateral movement speed of the spray gun is 500 mm / s.
5. The method for preparing a (NiCr-Cr3C2) / NiCr composite coating according to claim 4, characterized in that, The thickness of the NiCr transition layer is 50 μm.
6. The method for preparing a (NiCr-Cr3C2) / NiCr composite coating according to claim 1, characterized in that, The conditions for spraying NiCr-Cr3C2 are as follows: The powder feed rate is 56-60 g / min, the oxygen flow rate is 1920 LPM, the propylene flow rate is 7 LPM, the air flow rate is 26 LPM, the distance between the spray gun and the substrate is 300 mm, and the lateral movement speed of the spray gun is 500 mm / s.
7. The method for preparing a (NiCr-Cr3C2) / NiCr composite coating according to claim 6, characterized in that, The thickness of the NiCr-Cr3C2 working layer is 150 μm.
8. The method for preparing a (NiCr-Cr3C2) / NiCr composite coating according to claim 1, characterized in that, The steps of the annealing process are as follows: The substrate coated with NiCr transition layer and NiCr-Cr3C2 working layer was sealed and wrapped with Al2O3-SiO2 refractory mortar using the high-temperature embedding method, and then annealed at 700℃ for 120 min.
9. A (NiCr-Cr3C2) / NiCr composite coating, characterized in that, It is prepared by the preparation method according to any one of claims 1-8.
10. The (NiCr-Cr3C2) / NiCr composite coating according to claim 9, characterized in that, The hardness of the (NiCr-Cr3C2) / NiCr composite coating is 1242 HV. 0.2 Its toughness is 7.9 MPa·m 1 / 2 The wear rate is 0.37 × 10⁻⁶. -5 mm 3 / N·m.
Citation Information
Cited By
HVOF spray coating as well as preparation method and application thereof
CN121380818A
A kind of corrosion and wear resistant composite coating and its hypersonic flame spraying preparation method
CN122687110A
